Grundtvig set fra Sverige - Nielsen, Valdemar (Grundtvig-Studier, 1958)
Grundtvig as Seen From Sweden. By Valdemar Nielsen. In Sweden Grundtvig never had the same influence as in Norway, where from the middle of the 19th century a very considerable influence exercised by his ideas can be traced both in Church and school, and especially in the Folk-High-School. Sweden got its first Folk-High-Schools at about the same time as Norway, but they were much more independent of the Grundtvigian schools in Denmark, and in the Swedish Church Grundtvig’s ideas about the Church left practically no trace. However, a number of important individuals were interested in him and his influence in Denmark and in his extensive and many-sided work as an author, and referred to it with admiration and respect. This was already the case with regard to his earliest mythological, historical and poetic writings, which attracted the attention of the historian E. G. Geijer and the poet E. Tegner, among others: “Nordens Mythologi” (“The Mythology of the North” ), 1808, was referred to with respects in Sweden and appeared in a Swedish translation in 1818 and again in 1839, and “Verdens Krønike” (“World Chronicle” ), 1812, in spite of its derogatory references to Swedish cultural life, received criticisms in Sweden which showed more understanding than did those in Denmark. However, the one-sided character of Grundtvig’s writings for a good number of years after the great upheavel of his conversion to Christianity after 1810 proved to be too alien from Swedish life and hindered them from having any significant influence there. But when Grundtvig, especially after his journeys to England around 1830, had gained a wider horizon and developed the unique literary activity which produced “Nordens Mythologi 1832” , “Haandbog i Verdenshistorien, (“Handbook of World History” ), his writings about the Folk High-School and his great work as a hymn-writer, this was bound to attract attention in Sweden, too. When in 1839 he sat forth his idea of a great University common to the whole of Scandinavia, and similar to Oxford and Cambridge, at least one Swede, P. Wieselgren, who was later Dean at the Cathedral of Göteborg, was greatly taken by it, and his enthusiasm for it was certainly not altogether without significance in the establishment of the “Göteborgs högskola” (the present University of Göteborg), even if it became something quite different from what Grundtvig had in mind. In the movement for Scandinavian unity, which later found expression in joint student meetings and Church meetings, Grundtvig became a prominent figure, receiving admiration and homage from the Swedish delegates as well from the others, even if they were often without any deep understanding of his ideas about either the nation or the Church. Several described in strong terms the influence which Grundtvig had exercised upon them, both in private conversation and as a public speaker. But during the Scandinavian Church meetings it was noticeable that nearly all the Swedish delegates were without understanding of Grundtvig’s Church activities, and Swedish theological research also concerned itself very little with them, so that it is really only in the present century that an interest in them can be traced. Even a man like Archbishop Söderblom, who died in 1931, seems to have only noticed Grundtvig’s significance in the closing years of his life, but then gave him the rank of »prophet« in his last Gifford Lecture in Edinburgh in 1931. A Swedish theologian of the present day, Bishop Aulén, who in 1912 wrote about Grundtvig in a book on the Lutheran conception of the Church, states that he would now attach far more positive value to Grundtvig’s conception of the Church than he did then. Several Swedish Churchmen in recent times have declared that in Swedish Church life, and indeed in Protestant Church life as a whole, there is a need for some of the things which were called forth by Grundtvig’s influence in Danish Church life; and the much respected theologian from Uppsala, Prof. Anton Fridrichsen, who died in 1953, wrote in 1942 that Grundtvig, side by side with Luther, must be “ a guide to the new interpretation of Christ and the new conception of the Church for which the present age is thirsting and towards which the Church is striving.” The Swedish Folk High-School is by no means a direct imitation of the Danish one, but all the same Grundtvig is recognised in Sweden, too, as the originator of the Folk High-School, and they value the inspiration in its work which they have had from Denmark. And this was not forgotten when in 1943 they celebrated the 75th anniversary of the Folk High-School in Sweden. Nevertheless, a Swedish Folk High-School man wrote afterwards, “ In celebrating the 75th anniversary festival of the Swedish Folk High-School recently we Swedes might well have done more honour to ourselves by stressing a little more strongly the debt (which is fortunately ineffaceable) that our Folk High-School owes to the Danish Folk High-School and Grundtvig, without which it would, quite simply, never have come into existence - as a Folk High-School.” The High-School man just mentioned regrets, like several others, that Grundtvig is not better known in Sweden, but, unlike many others, he does not think that Grundtvig’s universe of thought must be so remote from modern Swedes as to be a hindrance to their understanding of him. Prof. Anton Fridrichsen considers, on the contrary, that perhaps there may be in Grundtvig’s whole personality something un-Swedish which makes it hard for him to be understood in Sweden. However, some people on the Swedish side have always worked to make him known in wider circles. They have not only translated Danish biographies, the latest of these to be translated being that by Prof. Hal Koch in 1941, but at intervals independent Swedish studies on Grundtvig and his work have appeared, the first, by Rev. P. G. Ahnfelt, in 1859. The one by the school headmistress, Anna Sandström, may be described as one of the most important; naturally enough, it deals specially with Grundtvig’s work for popular education, and calls him “ the greatest popular educator of the North.” This description of Grundtvig points out that, unlike many others who realised the splendour of the life of the spirit, he did not feel himself to be raised above the multitude, but devoted himself to ensuring that this education should bring benefits to the many. This makes his memory immortal. Right up to recent years, articles have appeared, in daily papers and periodicals, which deal with Grundtvig or aspects of his work and which show that in Sweden too, people are interested in it, and perhaps he has really had more significance for the Swedish people than a more superficial impression would indicate.